Corona Roja : Sobre el Volcán. - Bonito Oliva, Achille; Carracedo, Juan Carlos; Castro, Fernando; De Albinana, Salvador; Lozano, Luis-Martin; Moreno Villarreal, Jaime; Nazzaro, Antonio; Rivas, Francisco; Centro Atlántico de Arte Moderno, Las Palmas de Gran Canaria (Las Palmas de Gran Canaria : Centro Atlantico de Arte Moderno, 1996)
Alfonso, Bonifacio ; Alÿs, Francis ; Berlin, Dis ; Biasiucci, Antonio ; Bonk, Keiko ; Cardenes, Ricardo ; Castellano, Gennaro ; Dokoupil, Jiri Georg ; Elizondo, Arturo ; Galarza, Elena ; Gallardo, Tony ; Garduno, Flor ; Hidalgo, Juan ; Iglesias, Cristina ; Immendorff, Jörg ; Iturbide, Graciela ; José, Angeles San ; Jusidman, Yishai ; Klarwein, Mati ; Lootz, Eva ; Marón, Salvador ; Mataparda ; Monasterio, Pablo Ortiz ; Ocampo, Manuel ; Oehlen, Albert ; Ortiz, Rubén ; Plossu, Bernard ; Sáez, Manuel ; Salvo ; Schifano, Mario ; Scholte, Rob ; Schuyff, Peter ; Scianna, Ferdinando ; Stasio, Stefano Di ; Tatafiore, Ernesto ; Turrell, James ; De Vera, Cristino
biog., ind. tent., gr. tent., bibliog. p. 233-250
Engels
Spaans
Corona Roja : Sobre el Volcán, Centro Atlantico de Arte Moderno Las Palmas de Gran Canaria, 17.09.1996 - 17.11.1996
boek